2001
DOI: 10.1128/aac.45.2.532-539.2001
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties and Mode of Action of the Pyrrothine Holomycin

Abstract: Holomycin, a member of the pyrrothine class of antibiotics, displayed broad-spectrum antibacterial activity, inhibiting a variety of gram-positive and gram-negative bacteria, with the exception of Enterobacter cloacae, Morganella morganii, and Pseudomonas aeruginosa. The antibiotic lacked activity against the eukaryotic microorganisms Saccharomyces cerevisiae and Candida kefyr. Holomycin exhibited a bacteriostatic response against Escherichia coli that was associated with rapid inhibition of RNA synthesis in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 27 publications
(46 reference statements)
8
98
0
3
Order By: Relevance
“…These results suggest that introduction of 2,4-dimethoxyphenyl group to N-4 position is favorable. For R 3 R 2 N compounds, ethylamino group and diethylamino group were better for the activity, on the other hand, corresponding methylamino, bis (2-hydroethyl)amino, pyrrolyl, piperidyl, 2-hydroxyethylamino analogs (4,7,8,9,10) showed weak leukocyte-increasing activity, and the other heterocyclic derivatives (11, 12, 13) also did not display obvious leukocyte-increasing activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that introduction of 2,4-dimethoxyphenyl group to N-4 position is favorable. For R 3 R 2 N compounds, ethylamino group and diethylamino group were better for the activity, on the other hand, corresponding methylamino, bis (2-hydroethyl)amino, pyrrolyl, piperidyl, 2-hydroxyethylamino analogs (4,7,8,9,10) showed weak leukocyte-increasing activity, and the other heterocyclic derivatives (11, 12, 13) also did not display obvious leukocyte-increasing activity.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Dithiolopyrrolones have also been reported to have anticancer activity, [15][16][17] and shown potent membrane stabilization and platelet anti-aggregate activities. 18 We first reported that ZL-004 ( Figure 1) exhibited antileukopenia activity.…”
Section: Introductionmentioning
confidence: 99%
“…Both compounds demonstrated broad activity against bacterial and fungal RNAPs, and functional analysis showed that that they could inhibit bacterial transcription elongation and yeast transcription initiation (149)(150)(151).…”
Section: Inhibitors With Unknown Targetsmentioning
confidence: 99%
“…Thiolutin and holomycin are types of pyrrothine natural products isolated from Streptomyces luteosporeus and Streptomyces clavuligerus, respectively (148,149). Both compounds demonstrated broad activity against bacterial and fungal RNAPs, and functional analysis showed that that they could inhibit bacterial transcription elongation and yeast transcription initiation (149)(150)(151).…”
Section: Inhibitors With Unknown Targetsmentioning
confidence: 99%
“…11,12 In addition, 4 showed the inhibition of RNA synthesis, 11 and the calculate log P (ClogP) did not exceed 2.0. 13 These properties fascinated us to hybridize myxopyronins with the holothin molecule to expect the efficacy beyond our anticipations.…”
mentioning
confidence: 99%